2014
DOI: 10.1016/j.pharep.2014.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of nimesulide against hepatic ischemia/reperfusion injury in rats: Effects on oxidant/antioxidants, DNA mutation and COX-1/COX-2 levels

Abstract: Nimesulide at 100mg/kg prevented oxidative liver damage induced with I/R significantly better than at a dose of 50mg/kg. These experimental findings indicate that nimesulide may be useful in the treatment of hepatic I/R damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…Myeloperoxidase is an important enzyme that is found in neutrophils, and it is involved in the ROS production (26,27). In recent studies, in the hepatic I/R injury, it is often stated that as an indicator of neutrophil infiltration, an increase in the MPO activity causes the endothelial dysfunction and inflammation (28,29). Similarly, our study showed that HI increased the MPO values compared with the control group in the liver tissue, while in the SJW group in our study, the MPO activity was substantially reduced, and the results were close to the MPO values of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Myeloperoxidase is an important enzyme that is found in neutrophils, and it is involved in the ROS production (26,27). In recent studies, in the hepatic I/R injury, it is often stated that as an indicator of neutrophil infiltration, an increase in the MPO activity causes the endothelial dysfunction and inflammation (28,29). Similarly, our study showed that HI increased the MPO values compared with the control group in the liver tissue, while in the SJW group in our study, the MPO activity was substantially reduced, and the results were close to the MPO values of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, there is no study in the literature on the protective effect of nimesulide against small intestinal mucositis induced by MTX. However, there are some studies demonstrating that nimesulide protects gastric and hepatic tissues against oxidative stress at a dose of 100 mg/kg [8, 28]. It has been reported that nimesulide and its metabolites may prove useful in prevention of acute and chronic free radicals mediated tissue damage [16].…”
Section: Discussionmentioning
confidence: 99%
“…64 The toxicity of nimesulide to hepatocytes has been previously observed 65,66 which is attributed mainly to the nitro group in its structure. 67 After reduction, NiNH 2 exhibits reduced toxicity than nimesulide in hepatocytes because nimesulide is a powerful protonophoretic uncoupler and NAD(P)H oxidant.…”
Section: Cell Growth Inhibition By Ha-nimesulidementioning
confidence: 98%